Evaluating the Level of Total Mercury Present in the Soils of a Renowned Tea Production Region - Jinghua Xu; Ruijia Xie; Liping Liu; Zhiqun Huang (Agronomy)
Total mercury pollution in oolong tea garden soils was comprehensively investigated in this study. Soil samples were collected from 146 villages in a famous oolong tea production area. The total mercury content in the soils ranged from 0.025 to 0.296 mg/kg, with a median of 0.105 mg/kg. According to the Soil Accumulation Index Method, 67.81% of samples were pollution-free, 31.51% had pollution levels from none to moderate, and 0.68% were moderately polluted. The PMF model revealed that natural geochemical processes were the main mercury source, contributing 72.4%, with some from transportation, coal combustion, and industrial activities. Most values were below the HQ threshold, suggesting low non-carcinogenic risk from mercury in most soils. Further research is needed to understand mercury’s bioaccumulation in tea leaves and assess short- and long-term exposure risks for a better understanding of its long-term impacts on the tea industry and human health.